2016
DOI: 10.3892/ol.2016.4323
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metformin and salinomycin on transforming growth factor β-induced epithelial-to-mesenchymal transition in non-small cell lung cancer cell lines

Abstract: Abstract. The epithelial-to-mesenchymal transition (EMT) is highly involved in the development of metastases. EMT transforms epithelial carcinoma cells into mesenchymal-like cells, characterized by increased cell migration and invasiveness. Transforming growth factor β (TGFβ) appears to be crucial in this process. Metformin and salinomycin have demonstrated an EMT inhibitory effect. The current experiments indicate that these substances specifically inhibit TGFβ-induced EMT in non-small cell lung cancer (NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…The cell lines were cultured in Dulbecco's modified Eagle's medium (DMEM) with low glucose (GE Healthcare Life Sciences, vienna, Austria), supplemented with 10% fetal calf serum (FCS; Sigma-Aldrich, Munich, Germany) and 100 U/ml penicillin, 100 µg/ml streptomycin and 2 mM Lglutamine (PAA Laboratories; GE Healthcare Life Sciences). The cells were cultivated in cell culture flasks (Falcon ® ; Becton-Dickinson Austria GmbH, Schwechat, Austria) at 37˚C in an atmosphere of 5% CO 2 until the desired cell confluence for further experiments was reached (15).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The cell lines were cultured in Dulbecco's modified Eagle's medium (DMEM) with low glucose (GE Healthcare Life Sciences, vienna, Austria), supplemented with 10% fetal calf serum (FCS; Sigma-Aldrich, Munich, Germany) and 100 U/ml penicillin, 100 µg/ml streptomycin and 2 mM Lglutamine (PAA Laboratories; GE Healthcare Life Sciences). The cells were cultivated in cell culture flasks (Falcon ® ; Becton-Dickinson Austria GmbH, Schwechat, Austria) at 37˚C in an atmosphere of 5% CO 2 until the desired cell confluence for further experiments was reached (15).…”
Section: Sample Preparationmentioning
confidence: 99%
“…It blocks different types of tumor cell in the G0/G1 phase or inhibits the G1/S-phase transition in the cell cycle by regulating the expression of cell cycle proteins and their associated factors (25)(26)(27). Metformin also exerts a dose-dependent inhibitory effect on the proliferation of lung cancer cells of various pathological types (28,29). The mechanism may include the activation of the adenosine 5'monophosphate-activated protein kinase (AMPK) pathway (30,31), which reduces the proliferation of tumor cells by inhibiting epidermal growth factor receptor and insulin-like growth factor 1 receptor pathways (26,32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that Met reversed EMT phenotype induced with transforming growth factor beta 1 (TGF-β1) in breast, lung, and cervical cancer cells by targeting the mechanisms regulating the expression of E-cadherin. The exposition of tumor cells to Met resulted in suppression of their metastatic properties [8,38].…”
Section: Metformin Inhibits Epithelial-to-mesenchymal Transition (Emtmentioning
confidence: 99%